Reasoning and reversibility in capacity law - Hass, B (BMJ Publishing Group, 2022)
A key objective of the law in the assessment of decision-making capacity in clinical settings is to allow clinicians and judges to avoid making value judgements about the reasons that patients use to refuse treatment. This paper advances two lines of argument in respect of this objective. The first is that authorities cannot rationally avoid significant evaluative judgements in the assessment of a patient's own assessment of the facts of their case. Assessing reasoning is unavoidably value-laden. Yet the underlying motivation behind clinicians' and the law's value-neutral aims, ie, the avoidance of undue paternalism, is worth preserving. That being so, the second line of argument will try to show that that underlying motivation is better served in a limited range of cases by embedding a 'reversibility standard' in the assessment process so that the patient can, if they wish, and in due course, bring about the consequences that they were prevented from realising as a result of a determination of incapacity.